Tunka Advanced Instrument for cosmic rays and Gamma Astronomy - Kostiunin, Dmitriy; Astapov, I.; Bezyazeekov, P.; Borodin, A.; Budnev, N.; Brückner, M.; Chiavassa, A.; Dyachok, A.; Fedorov, O.; Gafarov, A.; Garmash, A.; Grebenyuk, V.; et al. (Deutsches Elektronen-Synchrotron, DESY, Hamburg, 2019)
18th International Baikal Summer School on Physics of Elementary Particles and Astrophysics, Bolshie Koty, Lake Baikal, Russia, 12 Jul 2018 - 21 Jul 2018; Journal of physics / Conference series Conference series [...] 1263, 012006 - (2019). doi:10.1088/1742-6596/1263/1/012006 : The paper is a script of a lecture given at the ISAPP-Baikal summer school in 2018. The lecture gives an overview of the Tunka Advanced Instrument for cosmic rays and Gamma Astronomy (TAIGA) facility including historical introduction, description of existing and future setups, and outreach and open data activities. : Published by IOP Publ.20382, Bristol